2009
DOI: 10.1002/nml.219
|View full text |Cite
|
Sign up to set email alerts
|

Survival in local voluntary associations

Abstract: Past analyses of organizational failure and success include studies of traditional social movements (Sandell, 2001;Stern, 1999), interest organizations Lowery, 1995, 1997;Haider-Markel, 1997;Nownes and Lipinski, 2005), and new social movements (Edwards and Marullo, 1995;Minkoff, 1993Minkoff, , 1997. Most of these, however, focus exclusively on factors outside the organization' s control or on organizational design and strategy. Some explore hypotheses derived from organizational ecology such as density depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 35 publications
1
40
0
1
Order By: Relevance
“…Previous studies (Wollebaek 2009) also indicated that a concentration usually occurs in both economic resources and the number of members to a small group of organizations. The third hypothesis posited that the largest voluntary associations would be more positive of both management more similar to a for-profit company and management with fewer democratic decision-making procedures.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies (Wollebaek 2009) also indicated that a concentration usually occurs in both economic resources and the number of members to a small group of organizations. The third hypothesis posited that the largest voluntary associations would be more positive of both management more similar to a for-profit company and management with fewer democratic decision-making procedures.…”
Section: Resultsmentioning
confidence: 93%
“…Because the previous studies in this area have tended to focus on larger confederate organizations (compare Einarsson 2012a(compare Einarsson , 2012bHvenmark 2008), it is unclear whether these studies outline a general trend that is valid even for small local voluntary associations in more rural areas. Previous studies have indicated that there may be a rural/urban divide in values among voluntary associations (Hooghe and Botterman 2012;Wollebaek 2009). Therefore, the following hypothesis is formulated:…”
Section: Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…• C. Finally, one last perspective discusses NPO sustainability in terms of success or failure [10,31,[75][76][77].…”
Section: Sustainability Approaches In Non-profit Organizationsmentioning
confidence: 99%
“…The locally precise, high-n data is, however, very well suited for the assessment of population ecological theory. Wollebaek (2009Wollebaek ( , 2010 shares this interest in social welfare policies but, in contrast the UK studies, theoretically relies on the organizational ecology tradition in among others social movement studies (Minkoff 1997). He is interested in the change in density and the turn-over / volatility of local populations of voluntary associations.…”
Section: Counting Organizations Per Typementioning
confidence: 99%